Purulent constrictive pericarditis caused by Salmonella enteritidis in a patient with adult-onset Still's disease: A case report. Issue 50 (December 2017) - Kuo, Chia-Cheng; Yu, Wen-Liang; Lee, Chen-Hui; Wu, Nan-Chun
Abstract: Rationale: Purulent pericarditis is a rare and usually fatal disease. Immunodeficiency state and preexisting pericardial effusion can predispose patients to infections. However, we are not aware of similar cases in patients with adult-onset Still's disease (AOSD). In addition, it is seldom caused by Salmonella bacteria. Patient Concerns: We report a 30-year-old woman with dyspnea on exertion and epigastric fullness. She was newly diagnosed with AOSD 4 months previously and medicated with prednisolone. Diagnoses: Transthoracic echocardiography (TTE) and computed tomography revealed a thickened pericardium with loculations in the pericardial space, consistent with purulent constrictive pericarditis. Subsequent cultures of blood and pericardial fluid yielded S enteritidis . Interventions: She underwent subtotal pericardiectomy through a limited median sternotomy, and antibiotic therapy (ceftriaxone) for 1 month. Outcomes: The New York Heart Association functional classification downgraded from class III to class I. There was no recurrence during the 1-year follow-up. Lessons: This case presents an opportunity to highlight the importance of considering purulent pericarditis in patients previously diagnosed with AOSD. High clinical suspicion, early diagnosis, and prompt management can result in a better outcome in purulent pericarditis.